Comparetive study between saline sonohysterography,transvaginal ultrasound and biopsy in evaluation of endometrial disease in postmenopausal bleeding - Ahmed, Laith (Journal of the Faculty of Medicine Baghdad, 2013)
Background : Transvaginal ultrasound is used conventionally as initial investigation of patients with postmenopausal bleeding, but saline contrast sonohysterography is a better technique to reliably distinguish focal from diffuse endometrial lesion.Patients and methods:     During the period from November 2011 to MAY 2012 ,40 female patients with postmenopausal bleeding were submitted to sequential examination by transvaginal ultrasound ,and sonohysterography .the presence of focal endometrial lesions and type of lesion (endometrial hyperplasia ,polyp, submucous myoma ,or malignancy )were noted .predictive values were calculated  by correlating the results with final diagnosis reached by endometrial biopsy.Objectives: to compare the ability of transvaginal ultrasonography and saline infusion sonohysterography as initial modality for the diagnosis of endometrial abnormalities in women with PMB by correlating the results with endometrial biopsy.Result:The sonohysterography had 89.4 % sensitivity and 90% specificity , DA 90%, compared to 60%sensitivity and 70%specificity achieved by transvaginal sonography .The diagnostic performance of sonohysterography for 3 main endometrial abnormalities (i.e. endometrial hyperplasia ,polyps and submucous  myoma ) was better than transvaginal sonography. The best results were seen in cases of submucos myoma where sensitivity and specificity of sonohysterography reached to 100% as compared to TVS (66% and 95.24% respectively).Conclusion:The results have substantiated that sonohysterography is a better tool than transvaginal sonography for the assessment of endometrial intra-cavity lesion .by providing accurate differentiation between focal and diffuse endometrial lesions.